Protein Electrophoresis Pattern and Oxidative Stress Protection of Human Follicular Fluid in Fertile and Infertile Women - Maryam Hasanpour; Mohammad Taghi Goodarzi; Mahnaz Nouri (Mashhad University of Medical Sciences, 2019)
Introduction: Epidemiological studies show that 10 to 15% of couples experience infertility worldwide. It is estimated that 40-50% of infertilities are related to female factors and 30% are male factors and others are attributed to both partners. Follicular fluid supplies an environment for ovulation and it reflects hormonal and biochemical activities of follicles in different stages. The effects of follicular fluid oxidative stress on ovum maturation and fertility are not well explained. Therefore, this study was performed with aim to evaluate and compare antioxidant properties of follicular fluid in healthy and infertile women and also, to examine the protein electrophoresis pattern of follicular fluid in these two groups.  Methods: This case-control and cross-sectional study was performed on 17 infertile women with ovulation disorder and 17 healthy women with infertility related to male factor who were candidate for IVF and had referred to Fatemeh-Zahra infertility center, Babol in 2018. Follicular fluid specimens were collected from 34 infertile and healthy women. To measure antioxidant properties, FRAP (Ferric reducing antioxidant power) and DPPH (1,1-Diphenyl-2-picryl-hydrazyl) tests were performed. Lipid peroxidation was assayed using MDA (Malondialdehyde) test. SDS-PAGE (sodium dodecyl sulphate-polyacrylamide gel electrophoresis) was used to evaluate protein electrophoresis pattern. Bradford method was used to assess total protein. Data were analyzed by SPSS software (version 16) and t-test. P<0.05 was considered statistically significant. Results: Antioxidant properties and lipid peroxidation assay did not show any statistical significant differences between two groups (p=0.23 and p=0.45, respectively). Also, the results of electrophoresis test and total protein were not significantly different between two groups (p=0.73). Most amount of proteins in both groups was observed in heavy band between 48 -75 Kilo Dalton region. Conclusion: Although there was difference in oxidative stress level between two groups, it was not statistically significant. It can be attributed to small sample size in each group. More close evaluation using 2-dimentional electrophoresis is needed to show difference in follicular fluid protein electrophoresis pattern.